Differential Genetic and Epigenetic Regulation of catechol-O-methyltransferase is Associated with Impaired Fear Inhibition in Posttraumatic Stress Disorder - Norrholm, Seth D.; Jovanovic, Tanja; Smith, Alicia; Binder, Elisabeth B.; Klengel, Torsten; Conneely, Karen; Mercer, Kristina B.; Davis, Jennifer S.; Kerley, Kimberly; Winkler, Jennifer A.; Gillespie, Charles F.; Bradley, Bekh; et al. (Frontiers in Behavioral Neuroscience, 2013)
The catechol-O-methyltransferase (COMT) enzyme is critical for the catabolic regulation of synaptic dopamine, resulting in altered cortical functioning. The COMT Val158Met polymorphism has been implicated in human mental illness, with Met/Met homozygotes associated with increased susceptibility to posttraumatic stress disorder (PTSD). Our primary objective was to examine the intermediate phenotype of fear inhibition in PTSD stratified by COMT genotype (Met/Met, Val/Met, and Val/Val) and differential gene regulation via methylation status at CpG sites in the COMT promoter region. More specifically, we examined the potential interaction of COMT genotype and PTSD diagnosis on fear-potentiated startle during fear conditioning and extinction and COMT DNA methylation levels (as determined using genomic DNA isolated from whole blood) . Participants were recruited from medical and gynecological clinics of an urban hospital in Atlanta, Georgia. We found that individuals with the Met/Met genotype demonstrated higher fear-potentiated startle to the CS- (safety signal) and during extinction of the CS+ (danger signal) compared to Val/Met and Val/Val genotypes. The PTSD+ Met/Met genotype group had the greatest impairment in fear inhibition to the CS- (p=.006), compared to Val carriers. In addition, the Met/Met genotype was associated with DNA methylation at 4 CpG sites, 2 of which were associated with impaired fear inhibition to the safety signal. These results suggest that multiple differential mechanisms for regulating COMT function – at the level of protein structure via the Val158Met genotype and at the level of gene regulation via differential methylation - are associated with impaired fear inhibition in PTSD.